The Transition to Democracy in Paraguay
XIV, 230 p.
Keywords: The transition to democracy in Paraguay has been one of the most difficult in Latin America. This book highlights the limitations of the process of democratisation in a country which lacked a previous democratic tradition and where the legacy of the harsh regime of Alfredo Stroessner (1954-89) is enduring. The book describes the nature of the Stroessner regime, examines the actors in the democratisation process, and shows how they influenced the policies of the transition governments.